Implementasi Algoritma Rabin-Karp dalam Pendeteksian Plagiarisme pada Dokumen Makalah Mahasiswa - Zidan, Muhammad Rohyan; Setiawan, Kiki (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Term papers are scholarly works prepared by students as part of their assessment in the educational process according to their academic level. Concerns about the increasing incidence of plagiarism in academic documents are becoming more significant. To assess the extent of plagiarism in a document, the use of a plagiarism detection system based on the Rabin-Karp algorithm is essential. This algorithm is employed to compare the similarities between a PDF document and existing sources, helping to identify patterns resembling the original references. This plagiarism detection system provides relevant data to measure the originality of a work and determine the necessary preventive or corrective actions. The data collection methods applied include literature review and interviews, while the system development follows the prototyping approach, which features clear, structured, and practical stages.